Sagwa, the Chinese Siamese cat - Tan, Amy.; Schields, Gretchen (New York : Simon & Schuster Books for Young Readers, 1994)
Ming Miao tells her kittens about the antics of one of their ancestors, Sagwa of China, that produced the unusual markings they have had for thousands of years.
"Previously published as the Chinese Siamese Cat"--T.p. verso.
Book Links (A.L.A.).
Child Study Children's Book Committee.
School Library Journal.
4.2
K-3
Keywords: Cats -- Fiction; Cats -- Fiction; China -- Fiction; China -- Fiction